1995
DOI: 10.1093/tropej/41.6.328
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Hepatitis A and Hepatitis B Virus Markers in Cases of Acute Sporadic Hepatitis and in Healthy School Children from North West India

Abstract: The pattern of viral markers in acute sporadic hepatitis in 329 children and those in 334 healthy school children from North West India were studied. Hepatitis A was found to be the commonest infection in sporadic cases (78 per cent). Of these, 86 per cent were under 10 years and 50 per cent less than 5 years of age. Hepatitis B was positive in 8 per cent, non-A non-B in 13 per cent, A as well as B in 1 per cent, and none had Delta virus infection. Viral markers in healthy school children showed anti-HAV IgG p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
2
13
1
Order By: Relevance
“…However, several authors have studied the pattern of anti-HAV IgG in healthy population. 16,17 On studying the trends of HAV infection in different age groups, it was found that as the age increased, 7%). Such trends showing a high incidence of HAV infection in less than 10 years of age is attributed to the fact that viral hepatitis A is predominantly an infection of childhood.…”
Section: Discussionmentioning
confidence: 99%
“…However, several authors have studied the pattern of anti-HAV IgG in healthy population. 16,17 On studying the trends of HAV infection in different age groups, it was found that as the age increased, 7%). Such trends showing a high incidence of HAV infection in less than 10 years of age is attributed to the fact that viral hepatitis A is predominantly an infection of childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis A virus (HAV) accounts for 60-80 per cent cases of clinical hepatitis in the developing countries 1 2 . The clinical course may vary from asymptomatic, acute self-limiting viral hepatitis to life threatening acute liver failure (ALF).…”
mentioning
confidence: 99%
“…6,11,12 We found male to female ratio of 1.45:1. Although a slight preponderance of male as compared to females which was different from Poddar U et al study, spectrum of sporadic acute viral hepatitis in Indian children where they found that male to female ratio of 2.3:1.…”
Section: Discussionmentioning
confidence: 69%
“…These findings are higher than the earlier studies in north Indian children by Tondon BN et al and a study by Thapa BR et al in which Hepatitis A was found 67% and 78% respectively. 5,6 Typhoid fever was found to be the second most important cause of hepatitis with the incidence of 5%. In the literature, it has been mentioned that typhoid hepatitis is an important cause of morbidity in patient with typhoid fever.…”
Section: Discussionmentioning
confidence: 99%